2015
DOI: 10.1155/2015/830219
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Ischemic Gangrene as a Complication of Hemodialysis Access

Abstract: Upper limb ischemia is a well-recognized complication of dialysis access creation but progression to gangrene is uncommon. We report a case of upper limb ischemic gangrene and discuss the lessons learned during the management of this case. Clinicians must be vigilant for this complication and they should be reminded that it requires urgent management to prevent tissue loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Upper limb gangrene commonly occurs as a result of fracture mismanagement by traditional bone setters (TBS) or in humeral head or neck fractures [1][2][3]. Less common causes include vascular cannulation for dialysis, arteriography, thrombolysis, arthroscopy of the shoulder joint, following intravenous injection of drugs and infections such as gas gangrene [4][5][6]. Rarely it is found as a consequence of trauma and one study found that serious distal ischemia is uncommon in upper limb injuries resulting from trauma [7].…”
Section: Introductionmentioning
confidence: 99%
“…Upper limb gangrene commonly occurs as a result of fracture mismanagement by traditional bone setters (TBS) or in humeral head or neck fractures [1][2][3]. Less common causes include vascular cannulation for dialysis, arteriography, thrombolysis, arthroscopy of the shoulder joint, following intravenous injection of drugs and infections such as gas gangrene [4][5][6]. Rarely it is found as a consequence of trauma and one study found that serious distal ischemia is uncommon in upper limb injuries resulting from trauma [7].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative diagnosis of vascular injuries is often delayed, in part because they are unexpected but also because the symptoms are subtle and easily overlooked because collateral circulation can mask signs of ischemia 1 . Doppler ultrasound and angiography can be used to evaluate arterial flow, with angiography the preferred method for localizing the site of injury 1 . This study presents 2 cases of 4-part proximal humerus fracture-dislocations and compares the outcomes of acute and delayed surgical management.…”
mentioning
confidence: 99%
“…Injury to the axillary artery is uncommon, representing only 15% to 20% of all upper limb arterial injuries 1 . Over 90% of arterial injuries arise from penetrating wounds and the remainder from blunt trauma, such as falls.…”
mentioning
confidence: 99%